The canonization of al-Bukhārī and Muslim : the formation and function of the Sunnī ḥadīth canon - Brown, Jonathan (Islamic history and civilization. Studies and texts,, 2007)
The two 'Authentic' ḥadīth collections of al-Bukhārī and Muslim are the most famous books in Islam after the Qur'ān - a reality left unstudied until now. This book charts the origins, development and functions of these two texts through the lens of canonicity. It examines how the books went from controversial to indispensable as they became the common language for discussing the Prophet's legacy among the various Sunni schools of law. The book also studies the role of the ḥadīth canon in ritual and narrative. Finally, it investigates the canonical culture built around the texts as well as the trend in Sunni scholarship that rejected it, exploring this tension in contemporary debates between Salafī movements and the traditional schools of law.